Menedżment : podstawy zarządzania - Korzeniowski, Leszek (Kraków : EAS, 2005)
Koncepcie spravovania
Marketing
Planovanie
Organizovanie
Motivovanie
Kontrolovanie
Organizácie
Keywords: ekonómia; manažment